2016
DOI: 10.1074/jbc.m115.710160
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Lumen Formation in a Three-dimensional Model of Mammary Morphogenesis by Transcriptional Regulator ID4

Abstract: Concomitant loss of lumen formation and cell adhesion protein CEACAM1 is a hallmark feature of breast cancer. In a threedimensional culture model, transfection of CEACAM1 into MCF7 breast cells can restore lumen formation by an unknown mechanism. ID4, a transcriptional regulator lacking a DNA binding domain, is highly up-regulated in CEACAM1-transfected MCF7 cells, and when down-regulated with RNAi, abrogates lumen formation. Conversely, when MCF7 cells, which fail to form lumena in a three-dimensional culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Two SNP rs42446897 (75% PPI) and rs42330036 (77% PPI) were identified on BTA 6 at 13.0 and 105.1 Mb, respectively. The SNP rs42446897 was located within an intron in the Calcium/Calmodulin Dependent Protein Kinase II Delta (CAMK2D) gene that has been implicated in various roles associated with heart function (Daniels et al, 2015) and lumen formation of mammary tissue (Nguyen and Shively, 2016). Single nucleotide polymorphism rs42446897 (77% PPI) was located in a non-coding region of the Collapsin Response Mediator Protein 1 (CRMP1) gene whose resulting protein was found expressed in the nervous system of humans.…”
Section: Resultsmentioning
confidence: 99%
“…Two SNP rs42446897 (75% PPI) and rs42330036 (77% PPI) were identified on BTA 6 at 13.0 and 105.1 Mb, respectively. The SNP rs42446897 was located within an intron in the Calcium/Calmodulin Dependent Protein Kinase II Delta (CAMK2D) gene that has been implicated in various roles associated with heart function (Daniels et al, 2015) and lumen formation of mammary tissue (Nguyen and Shively, 2016). Single nucleotide polymorphism rs42446897 (77% PPI) was located in a non-coding region of the Collapsin Response Mediator Protein 1 (CRMP1) gene whose resulting protein was found expressed in the nervous system of humans.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, the fine-tuning of the lumen formation program involves two negative acting signals. One is ID4, a transcription factor that can inhibit other transcription factors (26), and the other is miR-342 that negatively regulates both IRF-1 (38) and DNMT1 (49). The missing upstream regulator not mentioned in the earlier studies is likely CEACAM1.…”
Section: Discussionmentioning
confidence: 98%
“…In support of the second model, overexpression of miR-342 mimics in the lumen-enabled SW cells, abrogates lumen formation. In the accompanying article (49) we show that CEACAM1 can restore ID4 expression by an epigenetic mechanism. Because ID4 may regulate the levels of ID1-3, that in turn, regulate the levels of other transcription factors, the situation could be more complex (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium/calmodulin-dependent protein kinase type II delta (CAMK2D) is a tumor suppressor that mediates the anti-proliferative and differentiating, at least in part through actions of calcium transduction 18 , 19 . Interestingly, recent studies revealed that members of CAMK2 family were implicated in the regulation of epithelial to mesenchymal transition (EMT) process through activation of MAPK and Notch-1 pathways 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%